SARS-CoV-2 vaccine development - Plotkin, Stanley (Henry Stewart Talks, 2020)
Current efforts to develop a vaccine, Possible strategies for vaccine development, Possible seasonal variations in virus prevalence, When could a viable vaccine be expected?